Inflation and Monetary Pass-Through in Guinea - Blavy, Rodolphe (Washington, D.C. : International Monetary Fund, 2004)
The paper analyzes the dynamics of inflation in Guinea during 1992-2003 applying cointegration and error-correction modeling to a bivariate model that includes consumer price and monetary variables. The empirical results, based on quarterly data, confirm the existence of a long-run relationship between money supply and consumer prices. This paper argues further that the pass-through has increased in recent years. Short-term dynamics are shown to accentuate the long-run impact. Impulse response analysis shows that a shock in the money stock will have an increasing impact over two years and will then stabilize at a higher level.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet